Liquid‐Phase Exfoliated Indium–Selenide Flakes and Their Application in Hydrogen Evolution Reaction. Issue 26 (29th May 2018) - Petroni, Elisa; Lago, Emanuele; Bellani, Sebastiano; Boukhvalov, Danil W.; Politano, Antonio; Gürbulak, Bekir; Duman, Songül; Prato, Mirko; Gentiluomo, Silvia; Oropesa‐Nuñez, Reinier; Panda, Jaya‐Kumar; Toth, Peter S.; et al.
Abstract: Single‐ and few‐layered InSe flakes are produced by the liquid‐phase exfoliation of β‐InSe single crystals in 2‐propanol, obtaining stable dispersions with a concentration as high as 0.11 g L −1 . Ultracentrifugation is used to tune the morphology, i.e., the lateral size and thickness of the as‐produced InSe flakes. It is demonstrated that the obtained InSe flakes have maximum lateral sizes ranging from 30 nm to a few micrometers, and thicknesses ranging from 1 to 20 nm, with a maximum population centered at ≈5 nm, corresponding to 4 Se–In–In–Se quaternary layers. It is also shown that no formation of further InSe‐based compounds (such as In2 Se3 ) or oxides occurs during the exfoliation process. The potential of these exfoliated‐InSe few‐layer flakes as a catalyst for the hydrogen evolution reaction (HER) is tested in hybrid single‐walled carbon nanotubes/InSe heterostructures. The dependence of the InSe flakes' morphologies, i.e., surface area and thickness, on the HER performances is highlighted, achieving the best efficiencies with small flakes offering predominant edge effects. The theoretical model unveils the origin of the catalytic efficiency of InSe flakes, and correlates the catalytic activity to the Se vacancies at the edge of the flakes. Abstract : InSe flakes are produced by the liquid‐phase exfoliation of β‐InSe single crystals in 2‐propanol. The morphology of the as‐produced InSe flakes is controlled by ultracentrifugation. Hybrid single‐walled carbon nanotubes/InSe electrocatalysts for the hydrogen evolution reaction exhibit overpotentials of 549 mV (at pH = 1) and 451 mV (at pH = 14). A density functional theory model demonstrates the origin of the catalytic activity.